INISIASI ARAB SAUDI MENUTUP PLATFORM MEDIA AL-JAZEERA DALAM BLOKADE POLITIK QATAR TAHUN 2017 - Rananda Girindra D, A.A. Gde Agung; Putri, Penny Kurnia; Suwecawangsa, Adi P. (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT This research aims to explain what are the reasons behind the initiation of Saudi Arabia to shut down Al-Jazeera by using a qualitative explanative method. This Qatar owned media is a media that dare to criticize a government and provide a platform for opposition groups such as the Muslim Brotherhood. As a mass media, Al-Jazeera in fact has the power to shape the mindset of society and trigger political change in a country such as for example during the Arab Spring. Arab Spring is a large-scale pro-Democracy movement in the Arabian Peninsula that is able to change monarchical political systems in several regional countries. Therefore, researchers use the framework of The Power of Media and National Security to answer the problem formulation, researchers found that the power of Al-Jazeera can creates social-political instability, then it can threaten ideology and social identity as aspects of national security possessed by Saudi Arabia Keywords: Al-Jazeera, Saudi Arabia, Arab Spring, National Security, Muslim Brotherhood, The Power of Media